Nature of public relations practice among different types of organizations in Shanghai. - Liu, En Xi. (2008)
This thesis seeks to apply the following concepts to study public relations in Shanghai: 1) Models of public relations in different types of organizations; 2) The roles of individual public relations practitioners; 3) The impact of culture on public relations practice in Shanghai.